Service Management Audit of SIKUAT Using The ITIL 4 Framework - Darmawan, I Gede Hadi; Gunantara, Nyoman; Sudarma, Made (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
The Balinese Traditional Village of Financial Information Management System (SIKUAT) is a web-based information technology service used to manage the financial administration of 1,493 Traditional Villages in Bali. To ensure service quality, user convenience, and improved service performance aligned with user needs, it is necessary to conduct a service management audit on SIKUAT. This research focuses on auditing the service management of SIKUAT by adopting the ITIL 4 framework, particularly within the domains of continual improvement, service continuity management, and infrastructure and platform management. The assessment was carried out using the Capability Maturity Model (CMM) method through interviews and document analysis. The results of the audit indicate that the maturity level of the SIKUAT service is at level 3 (defined) with an average score of 3,86, while the capability level is at level 2 (managed). The continual improvement domain has the highest maturity level, reaching level 4, which indicates that the improvement processes are relatively well-directed. However, the service continuity management domain and the infrastructure and platform management domain still require serious attention to improve their maturity levels, which are currently still at level 3. This condition indicates the need for further improvements in service sustainability and infrastructure management. Based on the audit results, it is recommended to establish a comprehensive infrastructure maintenance policy, define standards for incident handling, and conduct regular evaluations of features and data security. The implementation of these recommendations is expected to enhance the efficiency and sustainability of the SIKUAT service, thereby supporting more transparent and accountable financial governance in Traditional Villages. In addition, this study may serve as a reference for the Provincial Government of Bali in improving the SIKUAT service.